Комп’ютерне моделювання режиму переривистих струмів електроприводу постійного струму з трифазним керованим випрямлячем - Ковальова, Ю.В. (Електротехніка і електромеханіка, 2018)
Режим переривистого струму вентильних електроприводів постійного струму з’являється в інтервалах неробочого ходу механізмів. Розрахунок ємності конденсаторів фільтру виконується через діюче значення змінної складової випрямленої напруги і тому виникає завдання розробки аналітичної методики для її розрахунку через коефіцієнт пульсацій напруги з урахуванням кута керування, електромагнітної сталої часу якоря і струму навантаження. Вираз для розрахунку коефіцієнта пульсацій напруги з урахуванням впливаючих факторів, отриманий методом планування експерименту на основі комп'ютерного моделювання в програмному пакеті Simulink, дозволяє визначити ємність конденсаторів фільтрів і підвищити ефективність електромеханічного перетворення електроенергії за рахунок зниження змінної складовою випрямленої напруги. Режим прерывистого тока вентильных электроприводов постоянного тока появляется в интервалах холостого хода механизмов. Расчет емкости конденсаторов фильтра выполняется через действующее значение переменной составляющей выпрямленного напряжения и поэтому возникает задача разработки методики для ее расчета через коэффициент пульсаций напряжения с учетом угла управления, электромагнитной постоянной времени цепи якоря и тока нагрузки. Выражение для расчета коэффициента пульсаций напряжения с учетом влияющих факторов, полученное методом планирования эксперимента на основе компьютерного моделирования в программном пакете Simulink, позволяет определить емкость конденсаторов фильтра и повысить эффективность электромеханического преобразования электроэнергии за счет снижения переменной составляющей. Introduction. The mode of intermittent current for DC motor with three-phase thyristor rectifier appears in the idle intervals of some mechanisms. Active and passive filters reduce the variable component of the rectified voltage. The capacitance of the capacitors filter is determined by the effective value of the variable component of the rectified voltage. Problem. Necessity of developing an analytical method for calculating the effective value of the variable component of the rectified voltage in the intermittent current mode, taking into account three parameters: the control angle, the electromagnetic time constant of the armature circuit and the load current. Purpose. To determine the dependence of the effective value of the variable component of the rectified voltage for three parameters in theintermittent current mode. Methodology. The effective value of the variable component of the rectified voltage is suggested to be determined through the voltage pulsations factor as the ratio of the effective value of the variable component of the rectified voltage to its constant component. The dependence of the pulsations factor from the parameters of the mode is determined using computer simulation of the mode for intermittent current. Results. The computer model is developed in the software package Simulink, which allows to change each parameter of the mode separately while stabilizing the other two. Numerical dependences of the pulsation factor on each parameter are obtained. The analytical dependence of the voltage pulsations factor on three influencing values was obtained by the method of experiment planning. Originality. For the first time, method has been developed for calculating pulsation factor of the rectified voltage and calculating the effective value of the variable component in the mode of intermittent currents, taking into account three parameters. Practical value. The proposed method will allow to rationally determine the capacity of the capacitors of active and passive filters and increase the efficiency of electromechanical power conversion by reducing the variable component of the rectified voltage.